Evaluation of Curtain Durability of Karst Dam Based on AHP-FCE Method - GUO Xiaojing; XIE Mengshan; CAO Lei; LIU Ziyan; JIANG Maiyong; LI Jinyou (Renmin Zhujiang)
Dam curtain in Karst area is vulnerable to failure under Karst water erosion.Therefore,scientific evaluation of curtain durability is the key to the safe operation of dams.Therefore,this paper first used the analytic hierarchy process to construct the criterion layer of design factor layer,construction factor layer and service environment layer,and calculated the weight of each index via relative scale.Secondly,the fuzzy comprehensive evaluation method (FCE) was used to deal with the qualitative and quantitative index values,with the curtain durability evaluation model of the Karst dam composed of 19 indexes constructed.Finally,the established evaluation model was adopted to comprehensively evaluate the curtain durability of typical Karst dams.The results show that the eigenvalues of the fuzzy judgment matrix are less than 0.1,indicating that each index reports reasonable weight distribution.The representative value of the comprehensive evaluation results of the curtain durability of the typical Karst dam is 0.569 6,which falls within the “excellent” grade.This shows that the curtain design and construction scheme of the project is feasible,and the current operation of the curtain is basically consistent with the evaluation results,that is,the curtain durability evaluation model of the Karst dam established in this paper is reasonable.The research results cast new light on the qualitative evaluation of the curtain durability of the Karst dam,and also provide a reference for the design and construction scheme of the curtain in the Karst area,the durability of the buildings in the Karst area,and the durability evaluation of the buildings in the non-Karst area.